WITHDRAWN: Malta tourism losses due to second wave of COVID-19 - Grech, Victor (Early Hum Dev, 2020)
This article has been withdrawn at the request of the author(s) and/or editor. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal